(untitled) (Docentes 2.0 Journal, 2024)
Mathematics education and second language learning are visible priorities within the Colombian education system. The general objective of the research was to evaluate pedagogical practices through the development of mathematical competencies from the treatment, formulation, and resolution of problems based on the implementation of the “Integrated Learning of Content and Foreign Languages” methodology. The research was based on the deductive method with a humanistic interpretive paradigm and a qualitative approach, with a narrative design of an event and an exploratory documentary type with a cross-section. The research sample is a group of forty fifth-grade students from the Escuela Normal Superior Educational Institution of Envigado. The technique used to collect data was documentary analysis, and the instrument used to collect information was thematic analysis. The analysis of the results took into account the documentary review, the pedagogical practices in fifth grade in mathematics, and the implementation of the CLIL methodology, establishing qualitative relationships and an analysis done narratively. In this way, it was established that implementing the CLIL methodology greatly impacts the development of mathematical competencies in problem-solving. In this sense, the research identified significant elements of implementing the CLIL methodology that contribute to considerably improving student learning in different areas of knowledge.